Biological funneling of phenolics from transgenic plants engineered to express the bacterial 3-dehydroshikimate dehydratase (qsuB) gene - Umana, German E.; Perez, Jose M.; Unda, Faride; Lin, Chien-Yuan; Sener, Canan; Karlen, Steven D.; Mansfield, Shawn D.; Eudes, Aymerick; Ralph, John; Donohue, Timothy J.; Noguera, Daniel R. (Frontiers in Chemical Engineering, 2022)
The economic and environmental sustainability of lignocellulosic biomass biorefineries is predicated on generating biofuels and bioproducts from cell-wall polysaccharide and lignin polymers. Historical efforts in plant genetic engineering have focused on the development of strategies that facilitate biomass deconstruction, with more recently efforts including the synthesis of high-value chemicals in planta. One such genetic modification is the expression of the bacterial quinate and shikimate utilization B (qsuB) gene that increases the accumulation of protocatechuic acid in lignocellulosic biomass. Herein, we evaluated the effectiveness of an alkaline pretreatment process to extract phenolics directly from wild-type and QsuB-transgenic lines of Arabidopsis, poplar, and sorghum, and then upgrade them to the polyester precursor 2-pyrone-4,6-dicarboxylic acid (PDC) with an engineered strain of Novosphingobium aromaticivorans. Protocatechuic acid extracted from all QsuB transgenic lines was found to be mostly in the glycosylated form. Glycosylated protocatechuic acid and other plant-derived phenolics were effectively metabolized by N. aromaticivorans, and PDC production was greatest using extracts from an Arabidopsis QsuB transgenic line (~5% w/w), followed by QsuB sorghum (~1.1% w/w), and QsuB poplar (~0.4% w/w) lines. The comparison of PDC production from wild-type and QsuB transgenic lines of Arabidopsis, poplar, and sorghum demonstrates the utility of a mild alkaline pretreatment to liberate phenolics from plant biomass that are either naturally present or that accumulate as a consequence of genetic engineering strategies. All QsuB transgenic lines outperformed their wild-type counterparts with respect to observed PDC yields. In addition, microbial funneling to PDC was effective even when most of the protocatechuic acid extracted was in glycosylated form, clearly demonstrating that this bacterium can metabolize these aromatic conjugates. These findings illustrate the benefits of combining plant and microbial engineering for bioproduct formation from phenolics in lignocellulosic biorefineries.